Role of inducible nitric oxide synthase in regulation of pulmonary vascular tone in the late gestation ovine fetus. - Rairigh, R L (1998)
Nitric oxide (NO) produced by NO synthase (NOS) modulates fetal pulmonary vascular tone and contributes to the fall in pulmonary vascular resistance (PVR) at birth. Although the inducible (type II) NOS isoform is present in human and rat fetal lungs, it is uncertain whether type II NOS activity contributes to vascular NO production in the fetal lung. To determine whether type II NOS is present in the ovine fetal lung and to study the potential contribution of type II NOS on the regulation of basal PVR in the fetus, we measured the hemodynamic effects of three selective type II NOS antagonists: aminoguanidine (AG), 2-amino-5,6-dihydro-6-methyl-4H-1,3 thiazine (AMT), and S-ethylisothiourea (EIT). Studies were performed after at least 72 h of recovery from surgery in 19 chronically prepared fetal lambs (133+/-3 d; 147 d, term). Brief intrapulmonary infusions of AG (140 mg), AMT (0.12 mg), and EIT (0.12 mg) increased basal PVR by 82, 69, and 77%, respectively (P < 0.05). The maximum increase in PVR occurred within 20 min, but often persisted up to 80 min. These agents also increased mean aortic pressure but did not alter the pressure gradient between the pulmonary artery and aorta, suggesting little effect on tone of the ductus arteriosus. Acetylcholine-induced pulmonary vasodilation remained intact after treatment with selective type II NOS antagonists, but not after treatment with the nonselective NOS blocker, nitro-L-arginine. Using Northern blot analysis with poly(A)+ RNA, we demonstrated the presence of two mRNA transcripts for type II NOS (4.1 and 2.6 kb) in the fetal lung. We conclude that the type II NOS isoform is present in the ovine fetal lung, and that selective type II NOS antagonists increase PVR and systemic arterial pressure in the late-gestation fetus. We speculate that type II NOS may play a physiological role in the modulation of vascular tone in the developing fetal lung.